Respuesta :

Answer:

([tex]\frac{2}{3}[/tex], 2 )

Step-by-step explanation:

Given the 2 equations

3x + [tex]\frac{1}{2}[/tex] y = 3 → (1)

6x - y = 2 → (2)

Multiplying (1) by - 2 and adding to (2) eliminates the term in x, that is

- 6x - y = - 6 → (2)

Add (2) and (3) term by term to eliminate x

- 2y = - 4 ( divide both sides by - 2 )

y = 2

Substitute y = 2 into either of the 2 equations and solve for x

Substituting into (2)

6x - 2 = 2 ( add 2 to both sides )

6x = 4 ( divide both sides by 6 )

x = [tex]\frac{4}{6}[/tex] = [tex]\frac{2}{3}[/tex]

Solution is ( [tex]\frac{2}{3}[/tex], 2 )

ACCESS MORE